The Impact of Organizational Culture and Work Discipline on Employee Performance at Slangit Village Office, Klangenan Subdistrict, Cirebon Regency - Ulfatun, Ulfatun; Sularmi, Lili (Transforma Jurnal Manajemen, 2025)
The purpose of this study was to analyze the influence of organizational culture and work discipline on employee performance at the Slangit Village Office, Klangenan District, Cirebon Regency. The research method used a quantitative approach with a saturated sampling technique, involving 32 respondents. The results showed that organizational culture had a significant effect on employee performance with a regression equation of Y = 8.480 + 0.798X1, a correlation coefficient of 0.740 (strong relationship), and a contribution of 54.8%. Work discipline also had a significant effect with a regression equation of Y = 11.723 + 0.708X2, a correlation coefficient of 0.592 (moderate relationship), and a contribution of 35.0%. Simultaneously, organizational culture and work discipline had a significant effect on employee performance with a regression equation of Y = -2.094 + 0.641X1 + 0.430X2, a correlation coefficient of 0.799 (strong relationship), and a contribution of 65.8%.